Проблемы создания инфраструктурных условий для развития торгово-экономических отношений Украины с ЕС и ТС: железнодорожный транспорт - Кравченко, О.А. (Економіка промисловості, 2013)
Розглянуто можливості розвитку залізничного транспорту в умовах геополітичного та геоекономічного вибору України: підписання Угоди про асоціацію між ЄС і Україною і приєднання до Митного союзу. Виділено існуючі та потенційно можливі проблемні аспекти функціонування галузі при реалізації цих альтернатив. Обґрунтовано необхідність урахування можливості виконання вимог, що висуваються, у тому числі й до залізничного транспорту при виборі напряму інтеграції.
Ключові слова: залізничний транспорт, інфраструктура, рухомий склад, інтероперабельність. Рассмотрены возможности развития железнодорожного транспорта в условиях геополитического и геоэкономического выбора Украины: подписание Соглашения об ассоциации между ЕС и Украиной и присоединение к ТС. Выделены существующие и потенциально возможные проблемные аспекты функционирования отрасли при реализации этих альтернатив. Обоснована необходимость учета возможности выполнения выдвигаемых требований, в том числе и к железнодорожному транспорту, при выборе направления интеграции.
Ключевые слова: железнодорожный транспорт, инфраструктура, подвижной состав, интероперабельность. Nowadays a problem of working out an effective model of development of rail transport in condition of the geopolitical and geo-economic choice of Ukraine is relevant. In the article the prospects of development of the railway sector of Ukraine are investigated with the existing alternatives: the signing of the Association Agreement between the EU and Ukraine, and the accession to the Customs Union.
The Association Agreement between the EU and Ukraine includes such limits: implementation of high-speed railways (during the five years period after the Agreement’s coming into force); implementation of the Directives (EU) and the Regulations (EU) to market and infrastructure access, technical and safety conditions, combined transport and other aspects of passenger traffic’s regulation. In the article it is substantiated an impossibility of the implementation of limits to high-speed railways and ensuring of interoperability of Ukrainian rail transport (infrastructure and rolling stock) during the period determined in this Agreement.
In the article the aspects of changing of Ukrainian railways interoperability after the Technical Regulations in countries of Customs Unioncoming into force are considered as well as the positive effects of enjoining or closer cooperation with CU: preservation of Ukrainian railway complex in the integrity, development of an effective program of renewal of rolling stockand modernization ofinfrastructure that will helpreturntransit flowsto Ukrainian railways and,consequently, increasing of GDP.
Based on the analysis carried out in the article the conclusions are made that (1) the development of directions of Ukraine’s integration should be based not only on the opening prospects, but also on considering the possibility of the fulfillment of requirements; (2) development strategy of rail transport should be based on the need for harmonization of working with both European railway systems, and the countries of the CIS, which will allow increasing the demand for Ukrainian railways and the efficiency of their operation; (3) prospects for the development of railway transport should be related to improving technical means of transport, infrastructure development, continued construction of new railways, and increasing their freight and passenger traffic; (4) the development of strategic and tactical plans for reforming industry should be implemented taking into account both the available sources of financial resources for their implementation, and the need to maintain the financial stability of the railway transport.
Keywords: rail transport, infrastructure, rolling stock, interoperability.